IJCM_40A: Process Evaluation of Routine Immunization in post pandemic period in districts of Assam - Nirmolia Nabanita; Mahanta Tulika Goswami; Barua Swarnali; Biswas Abhijit Basu (Wolters Kluwer Medknow Publications, 2024)
Background: Globally, immunization faced disruption in 2020, for COVID19. DPT3 coverage fell from 91% (2019) to 85% (2020) in India. Assam reports 67% coverage. Reasons were fear of contracting covid, challenges in community mobilisation, transportation restrictions, deployment to covid duty. Overburdened HCP were under stress affecting service. Capacity building gap was also associated with vaccine hesitancy. Objective: Process evaluation of routine immunization in post pandemic period in Assam. Methodology: The supportive supervision data generated from 1.04.2022 to 30.03.2023 covering all 33 districts of Assam about using MOHFW M&S tool. Data was analysed and descriptive statistics used. Results: Microplan was followed for service provision by 97.4% ASHA and 61.4% AWW. No IEC material displayed in 12.2% sites. Headcount survey data available in 88.9% sites. In 93.5% sessions, updated due list was found. Key messages were given in 84.9% of sites following immunization. Blank MCP/RI card was present in 75.1% sites. Hubcutter was not found in 4.1% sites. Other logistics available were; paracetamol 94%, Vitamin A 88%, spoon for Vitamin A 86.1%, red and black bag 85.5%, ORS 86.9%, and zinc 75.8%. Anaphylaxis kit available in 92% of which 83.5% were within expiry date. Handwashing with soap and water or hand sanitizer was practiced in 81.6% of sessions. Conclusion: Availability of logistics, manpower as per microplan, capacity building and effective communication needed for further improving the vaccination coverage.